MARIND (MALIND–ANIM) LANGUAGE PRESERVATION IN MERAUKE REGENCY, PAPUA, INDONESIA - Martha Betaubun; Desy Eva Laila Rokhmah (Masyarakat Linguistik Indonesia, 2021)
Indonesia is the largest island country with huge language diversity in the world. The latest data shows that over 700 indigenous languages are spoken across 34 provinces of the country. Statistics show that among those numbers, the largest number of indigenous languages exists in Papua province, which covers more than 300 languages. This qualitative study was conducted in Merauke Regency, Papua, the largest regency in Indonesia. It is located in the easternmost tip of Papua island. The study aimed to discover the existence of the Marind language or in local dialect known as Malind - Anim, one of the indigenous languages spoken by the native tribe of Merauke, and to find out the preservation effort that has been conducted in Merauke. The result of the study revealed that there have been many efforts conducted by the local government of Merauke Regency and the stakeholders to maintain the existence of Marind (Malind – Anim) Language. It was conducted through (1) Educational policy, (2) Marind (Malind – Anim) language habituation in public spaces such as announcement at the airport, Marind (Malind – Anim) language usage in the public banner, and greeting in Marind (Malind – Anim) Language in every formal meeting, (3) Broadcasting media, and (4) Language documentation in forms of songs and dictionary.